Shea should shape up! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
When the European Union decided in 2000 to allow chocolate to contain up to 5% vegetal fats other than cocoa butter, shea butter was proclaimed as a promising substitute. Two years later, this has not happened. Palm oil, though of lesser quality, is...